The Ghosts of Chroniclers Past: The Transmission and Legacy of the Chroniques of Jean Froissart in the Anchiennes Cronicques d’Engleterre compiled by Jean de Wavrin - Prud’Homme, Caroline (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2013)
Compared to Georges Chastellain or Jean Molinet, Jean de Wavrin is not a very well known figure of burgundian historiography; he is nonetheless the author of the Anchiennes cronicques d’Engleterre, an extensive historical compilation in six volumes that has not yet been edited in full. About 40% of the text is derived from the Chroniques of Jean Froissart. This article investigates the transmission and the transformation of Froissart’s Chroniques into the Wavrin compilation through a close reading of an episode (the Flemish wars of 1379-85, Froissart, Book II; Wavrin, volume III) in manuscript context. It evaluates the extent to which Wavrin is faithful to Froissart, and explores complex issues of manuscript transmission. This article also examines Wavrin’s compiling method and his interventions on his source text taking into account the impact of these interventions on the reader, and the relationship between the materiality of the manuscript and its content.